Genome-wide identification and expression analysis of the DA1-like gene family in melon (Cucumis melo) - Wang, Mingzhen; Wang, Rui; Zhang, Hualin; Wu, Qianxing; Dong, Mingming; Li, Yunhai; Wu, Lian; Yang, Xiaofeng (Frontiers in Plant Science, 2026)
The DA1 (DA means “large” in Chinese) -like gene family represents a class of key regulators that control organ and seed size in plants, yet its characteristics and functions in melon (Cucumis melo) remain unexplored. In this study, we performed a genome-wide identification and characterization of the CmDA1 gene family in melon. A total of four CmDA1 genes were identified and found to be unevenly distributed across chromosomes 3, 8, 10, and 11. Phylogenetic analysis grouped the CmDA1 genes into three distinct subgroups with their orthologs from Arabidopsis thaliana (Arabidopsis) and Oryza sativa (rice). Structural analysis revealed high conservation within subfamilies, particularly in the characteristic UIM and LIM domains. The presence of hormone-responsive cis-elements, combined with divergent gene structures, suggests complex transcriptional regulation of the CmDA1 genes. Expression profiling based on RNA-seq data and qRT-PCR validation demonstrated that CmDA1 genes exhibit tissue-specific and fruit development-stage-specific expression patterns. Notably, CmDA1–3 showed broad and high expression across multiple vegetative tissues and maintained consistently high expression throughout fruit development from 2 to 50 days after pollination. These findings provide a foundational resource for the DA1 family in melon and position CmDA1–3 as a priority candidate for functional validation of its role in fruit size regulation.